A Tale Within a Tale: Mise en Abyme Adaptations of the Twenty-First Century - Flegar, Željka (Anafora, 2023)
In accord with the promise made by Henry Jenkins that “old and new media will interact in ever more complex ways” (Convergence Culture 6), this research observes metamodern fairy tale adaptations of the twenty-first century in light of Christina Bacchilega’s construct of the fairy-tale web and Henry Jenkins’ theory of convergence culture and transmedia storytelling. The research will address the growing trend of embedding “wonder tale” collections within the context of a larger narrative as an artefact of significance, power, and material value. Although original tales with known authorship, these fairy tale adaptations are appended to the mythology and culture of the fantastic secondary worlds. Such texts tend to be parodic, subversive, and even carnivalesque (Bakhtin; Stephens), providing a commentary on the culture of their origin, as well as our own. By blending cultures, styles, and formats, mise en abyme wonder tales also result in the empowerment of specifically marginalised groups. Generally defined as spin-offs that are otherwise a part of a complex inter- and hypertextual web, these fairy tale collections constitute a metafictional body of knowledge and wisdom. In the digital era much focus is placed on multimodal, hypertextual, and transmedia narratives with a significant influence of fandom on the production of such literary works. The study will focus on the popular examples of such practice, J.K. Rowling’s Tales of Beedle the Bard (2007/2008) and Ransom Riggs’ Tales of the Peculiar (2016), in order to define mise en abyme fairy tale adaptations, as well as to discuss their cultural significance and function.